Analysis of Seismicity Level and Coulomb Stress Changes in the Central Sulawesi Region in 1996-2022 - Lailatul Husna Lubis; Ratni Sirait; Dhiau Rahman Fikri (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
Central Sulawesi is an area that is prone to earthquakes. The movement of the Palu Koro Fault is the trigger for most of the destructive earthquakes in the Central Sulawesi region. This study aims to analyze seismicity based on the seismotectonic parameter b-value, analyze coulomb stress changes and based on the seismicity level analyze the risk of earthquakes in Central Sulawesi in the 1996-2022 range. This study uses data from the 1996-2022 earthquake catalog from the USGS catalog. Data from the USGS catalog was then processed using Zmap v6 based on MATLAB to obtain the b-value seismicity parameter using the maximum likelihood method. Data processing for coulomb stress is processed using MATLAB based Coulomb 3.4.2 software. Based on the results of the analysis, the b-value in zone 1 to zone 3 is 0.653 – 0.777. The results of the analysis of changes in coulomb stress obtained positive coulomb stress changes indicated by the red lobe with  a value of 1 to 8 bar and negative coulomb stress changes indicated by the blue lobe with a value of -1 to -8 bar. The results of the analysis of b-value and coulomb stress showed that the b-value obtained was relatively  low and correlated with a high level of change in coulomb stress. In general, earthquake-prone areas are located in the western and eastern parts of Central Sulawesi.